ANALISIS MANAJEMEN ASET PADA BADAN PEMBERDAYAAN MASYARAKAT, PEMERINTAHAN DESA, KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN KABUPATEN SUMEDANG - Nurhalimah Wulandini (JRPA - Journal of Regional Public Administration, 2018)
This study aims to analyze the problems of asset management, supporting factors in the asset management process, inhibiting factors in the asset management process and efforts to overcome asset management obstacles in the Community Empowerment Agency, Village Government, Family Planning and Women's Empowerment in Sumedang Regency. The method used in the preparation of this thesis is a qualitative research method, with an independent variable, namely asset management. The sampling technique used is purposive sampling, which is a sampling technique for data sources with certain considerations. Which is used as a source of data / informants are: Head of the General Staffing and Asset, Staff of Goods Managers, Staff of Goods Storage and Staff of Operators. In analyzing the data used the Miles and Huberman model with the steps: Data reduction, Data presentation, Conclusion Drawing/Verification, and Triangulation. Based on the results of interviews and observations which were then analyzed by data, it was concluded that supporting the existence of asset management is seen from the condition of assets, management of asset documents and supervision and control of assets. As for the process of asset management in Sumedang Regency BPMPDKBPP can be said to have been implemented well because researchers can see in the process of asset inventory, legal audit, asset assessment, asset optimization as well as asset monitoring and control. Although there are several things that become obstacles in the process, namely recording the accuracy of the number of goods, recording mutations of goods, transfer of assets that have not been optimal and supervision in asset management.